Perioperative intravenous lignocaine infusion for postoperative pain control in patients undergoing surgery of the spine: protocol for a systematic review and meta-analysis. Issue 10 (13th October 2020) - Licina, Ana; Silvers, Andrew
Abstract : Introduction: Intravenous lignocaine is an amide local anaesthetic known for its analgesic, antihyperalgesic and anti-inflammatory properties. Administration of intravenous lignocaine has been shown to enhance perioperative recovery parameters. This is the protocol for a systematic review which intends to summarise the evidence base for perioperative intravenous lignocaine administration in patients undergoing spinal surgery. Methods and analysis: Our primary outcomes include: postoperative pain scores at rest and movement at predefined early, intermediate and late time points and adverse events. Other outcomes of interest include perioperative opioid consumption, composite morbidity, surgical complications and hospital length of stay. We will include randomised controlled trials, which compared intravenous lignocaine infusion vs standard treatment for perioperative analgesia. We will search electronic databases from inception to present; MEDLINE, EMBASE and Cochrane Library (Cochrane Database of Systematic Reviews and CENTRAL). Two team members will independently screen all citations, full-text articles and abstract data. The individual study risk of bias will be appraised using the Cochrane risk of bias tool. We will obtain a risk ratio or mean difference (MD) from the intervention and control group event rates based on the nature of data. We will correct for the variable measurement tools by using the standardised MD (SMD). We will use a random-effects model to synthesise data. We will conduct five subgroup analysis: major versus minor surgery, emergency versus elective surgery, patients with chronic pain conditions versus patients without, duration of lignocaine infusion and adult versus paediatric. Confidence in cumulative evidence for will be classified according to the Grading of Recommendations, Assessment, Development and Evaluation system. We will construct summary of findings tables supported detailed evidence profile tables for predefined outcomes. Ethics and dissemination: Formal ethical approval is not required as primary data will not be collected. The results will be disseminated through a peer-reviewed publication. PROSPERO registration number: CRD420201963314